(untitled) (Environment & Health, 2016)
Objective. We studied the features of the morbidity level formation among the senior pre-school age children residing in the different districts from the ecological point of view. Materials and methods. We examined the children aged 5-6 years residing and attending pre-school institutions located in different ecological conditions: along the large highways, near industrial enterprises and in relatively pure district in Kyiv. Our materials were obtained with the help of the copy of the data from the primary medical documents at pre-school institutions and surveys of the parents on the development and child’s health state at the early stage of ontogenesis. Assessment of the organism resistance was performed on the basis of the determination of multiplicity and duration of acute respiratory infections. Results. The obtained results demonstrate that a morbidity formation significantly depends on the ecological conditions in the places of residence.The morbidity formation is the most intensive at the territories located along the large highways: the morbidity level in the children of these pre-school institutions increases the similar one in the districts near the industrial enterprises by 1.76 fold, in the relatively pure district – by 1.91 fold. The highest proportion of the children which were often ill for a long time and low resistant to the acute respiratory diseases were also revealed at the pre-school institutions located along the highways. So now it is necessary to renew a preventive sanitary inspection for the location of pre-school institutions and environmental control, just the ambient air in the places of their location.